PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS PEMECAHAN MASALAH BERBANTUAN ADOBE CAPTIVATE MATERI MATRIKS DI SEKOLAH MENENGAH KEJURUAN (SMK) 3 KOTABUMI - Rahmawati, Nisa Umi; Nugroho, Purna Bayu; Dinata, Karsoni Berta; Truong, Anh Thi Thuy (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Background. Technological advances and developments in the modern era like today are creating new mindsets and patterns of behavior in society. This also affects development in the field of education. Many studies have been carried out but only focus on utilization. Research Methods This research is a Research and Development (R&D) study which aims to develop problem-solving based learning videos. Data analysis in this study used descriptive analysis where the validation results were the quality of the development results. Research Results The results of the final assessment by material experts were 77.5% and with the criteria of